Characterizing Readiness for Advance Care Planning From the Perspective of Residents, Families, and Clinicians: An Interpretive Descriptive Study in Supportive Living. (18th February 2017) - Shaw, Marta; Hewson, Jennifer; Hogan, David B; Raffin Bouchal, Shelley; Simon, Jessica
Abstract: Background and Objectives: Advance care planning (ACP) involves reflection on health care preferences and communication of the person's wishes in case of future incapacity. ACP is particularly pertinent in supportive living (SL) as residents are at high risk of cognitive decline and changes in health status, but the readiness of residents, families, and health care practitioners to engage in ACP discussions is not known. The purpose of this study was to explore the readiness among these stakeholders and the factors that influence the degree of readiness. Research Design and Methods: Twenty-seven participants (10 residents, 8 family members, 9 health care practitioners) affiliated with 4 SL facilities in Calgary, AB, Canada took part in semistructured, one-on-one interviews. An interpretive descriptive approach was utilized to generate clinically relevant findings. Results: Variability in the conceptualization of ACP, including confusion regarding terminology, emerged as a major theme. Themes that influenced readiness for engagement in ACP discussions included the influence of prior experience for residents and family members, perception of treatment goals, and understanding of roles in the process between the groups. Discussion and Implications: Recommendations for clinicians include clarifying ACP concepts for themselves and residents, shifting focus toward an elucidation of values and preferences rather than on documentation, greater clarity about the roles of the various stakeholders, and recognizing the importance of prior experience for residents and family members. These findings can be used to contribute to the understanding of ACP engagement in SL and inform an approach to engaging in meaningful discussions about ACP.